Photography of Modernism and Postmodernism. Theory and the Ways of Representation - Matić, Jelena (Actual Problems of Theory and History of Art, 2013)
During the modernism photography became an essential medium for the fashion, advertising, magazines, journalism. The number of photographers, photo groups and movements increased. The photography, especially then due to the new unusual techniques (solarisation, montage, pho-togram, etc.) became very popular among avant-garde artists. Some art institutions, as Museum of Modern Art in New York, have established departments of photography. Despite all of this in practice and in theory of modernism photography has not got the same status as other forms of art. This situation has changed in the last three decades of the 20th c. with structuralism and post-structuralism, semiotic, feminism, conceptual and post-modern art when technical media became very popular in artistic practice. In this paper I will try to pinpoint the most important theories of photography in modernism and post-modernism.
Keywords: photography; theory; structuralism; modernism; post-modernism; post-structuralism; conceptual art; Clement Greenberg; Roland Barthes; Victor Burgin